Blake's Pouch Cyst: A Case Report - Verma, Saurabh Kumar; Sridhar, M. S.; Shashivadhanan, S.; Garg, Manish (Indian Journal of Neurosurgery, 2017)
It is a rare and underdiagnosed entity. The adagium “one only sees what one knows” is certainly true in cases of Blake's pouch cyst, as all types of posterior fossa cysts and cyst-like malformations may present nearly identical on initial imaging studies. Only one case of Blake's pouch cyst has been reported from this country, except for a case in utero, in which a diagnosis of Blake's pouch cyst was made on prenatal ultrasound and later confirmed by MRI. In this report we describe a case of Blake's pouch cyst in a 9-month-old male child along with the principles of diagnosis of Blake's pouch cyst, in combination with literature review. Differentiating Blake's pouch cyst from other posterior fossa cysts and cyst-like malformations and recognizing the accompanying hydrocephalus that are essentially noncommunicating have important implications not only on clinical management but also on genetic counseling, which is unnecessary in case of Blake's pouch cyst.
Keywords: Blake's pouch cyst; posterior fossa; inferior medullary velum